2019
DOI: 10.3390/toxins11050278
|View full text |Cite
|
Sign up to set email alerts
|

Using Advanced Spectroscopy and Organic Matter Characterization to Evaluate the Impact of Oxidation on Cyanobacteria

Abstract: Drinking water treatment plants throughout the world are increasingly facing the presence of toxic cyanobacteria in their source waters. During treatment, the oxidation of cyanobacteria changes cell morphology and can potentially lyse cells, releasing intracellular metabolites. In this study, a combination of techniques was applied to better understand the effect of oxidation with chlorine, ozone, potassium permanganate, and hydrogen peroxide on two cell cultures (Microcystis, Dolichospermum) in Lake Champlain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Additionally, oxidation may further hinder the ability to identify cells because of its impact on the cell structure. Oxidation at higher dosages can cause significant morphological deformation of the cyanobacteria species, especially for H 2 O 2 and KMnO 4 in our study [ 63 ]. Flow cytometry conducted using the method described by Moradinejad et al (2019) showed partial membrane damage (up to 80%) under the soft-oxidation conditions performed in this study (data not shown) [ 63 ].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, oxidation may further hinder the ability to identify cells because of its impact on the cell structure. Oxidation at higher dosages can cause significant morphological deformation of the cyanobacteria species, especially for H 2 O 2 and KMnO 4 in our study [ 63 ]. Flow cytometry conducted using the method described by Moradinejad et al (2019) showed partial membrane damage (up to 80%) under the soft-oxidation conditions performed in this study (data not shown) [ 63 ].…”
Section: Resultsmentioning
confidence: 94%
“…Unlike 1 August, the Shannon diversity is no longer correlated with Dolichospermum . These differences could reflect the morphological differences between the dominant genera ( Microcystis vs. Dolichospermum) as a unicellular aggregate that are less resistant to oxidation as compared to filaments [ 63 ]. Chlorine and KMnO 4 exposures had a low impact on Microcystis and Dolichospermum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, guidance for the application of pre-oxidants during a cyanobacteria bloom is warranted. While previous studies have generally assessed the complete oxidation of cyanobacteria cells and release of cyanotoxins, particularly with respect to microcystin [12][13][14][15][16][17][18][19], low oxidant exposures (concentration × time (CT)) resulting in incomplete cell oxidation continue to require further examination. Furthermore, delayed release has been observed up to 120 min after the chlorination of cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies of drinking water treatment, flow cytometry was increasingly used for detecting cell activity and membrane integrity after oxidation processes ( Moradinejad et al, 2019 , Wert et al, 2013 , Xie et al, 2013 ). Wert et al used a flow cytometer along with chlorophyll-a measurements to investigate cyanobacterial cell damage and lysis ( Wert et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%